2017
DOI: 10.1016/j.jcf.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing endpoints for prospective studies of pulmonary exacerbation treatment response in cystic fibrosis

Abstract: Results from randomized prospective superiority and non-inferiority studies employing mean CRISS and FEV change from treatment initiation should prove compelling to the community. They will need to be large, but appear feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 29 publications
5
39
0
Order By: Relevance
“…In the current analysis, we have asked how risk factors associated with failure to return to baseline lung function differ by magnitude of ppFEV 1 drop before PEx diagnosis and treatment. Our observation of one in ten PEx having no pretreatment ppFEV 1 drop is similar to the 12.1% incidence of such events reported in the prospective STOP study (NCT02109822) when a 1‐year baseline calculation was employed . Interestingly, more than one‐third of these events in our study had a ppFEV 1 below baseline at follow‐up.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the current analysis, we have asked how risk factors associated with failure to return to baseline lung function differ by magnitude of ppFEV 1 drop before PEx diagnosis and treatment. Our observation of one in ten PEx having no pretreatment ppFEV 1 drop is similar to the 12.1% incidence of such events reported in the prospective STOP study (NCT02109822) when a 1‐year baseline calculation was employed . Interestingly, more than one‐third of these events in our study had a ppFEV 1 below baseline at follow‐up.…”
Section: Discussionsupporting
confidence: 87%
“…Evaluations of PEx treatment response using baseline ppFEV 1 recovery at follow‐up have often emphasized ppFEV 1 relative drops of more than 10% and excluded those PEx where an individual's ppFEV 1 at diagnosis is not less than their baseline value, because for those patients ppFEV 1 “recovery” has apparently occurred before treatment. Interestingly, these types of PEx are not particularly rare: a prospective observational study reported that 12.1% of patients were admitted to hospital for PEx with a ppFEV 1 exceeding their best recorded in the prior year and 19.6% exceeding their best in the prior 6 months . In this study, we examined the factors associated with a return to baseline ppFEV 1 not only in those PEx with a ≥10% pretreatment ppFEV 1 drop but also those with <10% and no ppFEV 1 drop.…”
Section: Introductionmentioning
confidence: 99%
“…84 Clinicians and patients seem to assign different priorities to resolution of symptoms, improvement in quality of life, and time to relapse as outcomes of interest. 82,84,85 The choice of primary outcome is important-for example, length of treatment is often driven by return of ppFEV1 or symptoms to baseline, so a rapid response could lead to a shorter treatment regimen, but a study of predictors of IV retreatment within 30 days following treatment for a PEx found treatment duration <9 days to be a risk factor. 80 Despite the unknowns, it is clear that antibiotic treatment of PEx is more likely to lead to recovery and preservation of lung function.…”
Section: Treatment Of Pulmonary Exacerbationsmentioning
confidence: 99%
“…However, there is evidence that such an approach may be misleading: exacerbating patients treated with intravenous (IV) antibiotics for less than 9 days (presumably because of an observation of rapid response) are at about double the risk of being retreated within 30 days as their peers treated longer with IV antibiotics, irrespective of other risk factors [7]. Further, it has been demonstrated that some patients continue to recover pulmonary function and experience reduced signs and symptoms of exacerbations for weeks after treatment stops (and unfortunately, the health of others degrades shortly after treatment cessation) [7,9,10]. Thus, clinical presentation immediately at the end of treatment may not accurately reflect clinical status even weeks after treatment.…”
Section: Comparisons Of Acute Treatments For Pulmonary Exacerbationsmentioning
confidence: 99%
“…This initial study was completed in 2016 [11,12]. Surveys of clinician and patient treatment goals were also collected and, in combination with treatment responses, sample size requirements and relative strengths and weaknesses of different possible efficacy endpoints for prospective randomized comparative trials of exacerbation treatments were delineated [10]. Currently, a larger, innovative multicenter study (STOP2; NCT02781610), in which IV antibiotic treatments of 10, 14, and 21 days in adults with CF will be compared is in active enrollment [13].…”
Section: Comparisons Of Acute Treatments For Pulmonary Exacerbationsmentioning
confidence: 99%